Numerical analysis of a counter-flow wet cooling tower and its plume. (May 2022) - Zargar, A.; Kodkani, A.; Peris, A.; Clare, E.; Cook, J.; Karupothula, P.; Vickers, B.; Flynn, M.R.; Secanell, M.
Abstract: A one-dimensional model to study the heat and mass transfer inside and immediately above a wet counter-flow cooling tower is described. The wet cooling tower thermodynamic model assigns zone-specific Merkel numbers to each of the rain, fill, and spray zones, and it includes an atmospheric plume model. Using the present formulation, zone-by-zone rates of heat rejection and water evaporation can be estimated, as can the visible plume height. The model is validated against the well-established Poppe and Merkel methods as well as select field data. Cooling tower performance and plume visibility are evaluated under a variety of climatic conditions (hot-dry, hot-humid, cool-dry and cool-humid), cooling tower designs (e.g. fill zone height, H f z ), and operating conditions (e.g. water-to-air mass flow rate ratio, L / G ). The parametric study in question highlights the ability of the proposed model to predict the impact of ambient conditions, cooling tower design parameters, and operating conditions on overall performance and patterns of atmospheric dispersion. The proposed model is ideal for numerical optimization of cooling towers that need to meet stringent thermal performance and plume visibility requirements. Highlights: A coupled one-dimensional cooling tower and plume model is developed. Heat transfer in each zone of the tower analyzed at varying ambient conditions. Plume visibility at different air flow rates studied at varying ambient conditions.